2019
DOI: 10.1016/j.labeco.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment expectations: A socio-demographic analysis of the effect of news

Abstract: In this study, we evaluate the effect of news on consumer unemployment expectations for sixteen socio-demographic groups. To this end, we construct an unemployment sentiment indicator and extract news about several economic variables. By means of genetic programming we estimate symbolic regressions that link unemployment rates in the Euro Area to qualitative expectations about a wide range of economic variables. We then use the evolved expressions to compute unemployment expectations for each consumer group. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 98 publications
2
10
0
1
Order By: Relevance
“…The lowest forecast errors are obtained for the households within the first quartile regarding income (RE1), the respondents with secondary education (ED2) and the unemployed (PR0). These results are in line with those obtained by Sorić et al (2019), who found that unemployed respondents' expectations were most accurate that those obtained by employed respondents. Behavioural economics offers a plausible explanation for this pattern through the "availability heuristic" (Kahneman and Tversky, 1974).…”
Section: Fig 2 Histogram With Mean Frequency For Each Survey Variablesupporting
confidence: 91%
“…The lowest forecast errors are obtained for the households within the first quartile regarding income (RE1), the respondents with secondary education (ED2) and the unemployed (PR0). These results are in line with those obtained by Sorić et al (2019), who found that unemployed respondents' expectations were most accurate that those obtained by employed respondents. Behavioural economics offers a plausible explanation for this pattern through the "availability heuristic" (Kahneman and Tversky, 1974).…”
Section: Fig 2 Histogram With Mean Frequency For Each Survey Variablesupporting
confidence: 91%
“…Similarly, Juhro and Iyke (2019) showed that accounting for consumer and business sentiments improved forecast accuracy of consumption in Indonesia. Gayer, and Reuter (2015) and Sorić et al (2019) obtained similar results for the EA. Claveria, Monte and Torra (2017a,b;2018, 2019a have used the survey expectations from the World Economic Survey carried out by the Ifo Institute to show their good forecasting performance when used to construct economic indicators.…”
Section: Cons11mentioning
confidence: 54%
“…Against this backdrop, the analysis of unemployment expectations and uncertainty seems more timely than ever before. Despite the existence of a huge and growing literature on the impact of economic uncertainty on activity (Baker et al 2016;Carriero et al 2018;Ghirelli et al 2021;Škrabić Perić and Sorić 2018), its impact on unemployment has been somehow relegated to the background, in a similar way to unemployment expectations (Abberger 2007;Sorić et al 2019). Some exceptions are the works of Caggiano et al (2014Caggiano et al ( , 2017, Choi and Loungani (2015), Netšunajev and Glass (2017) and Nodari (2014), which empirically confirm the contribution of economic uncertainty shocks to the volatility of unemployment, especially during recessions.…”
Section: Introductionmentioning
confidence: 98%